Circular economy model: Integrating BSF maggot and tilapia cultivation for organic waste management in vocational schools - Sulistyowati, Fitria; Septiani, Devi; Setyaningsih, Rina; Wati, Ika Wahyu Kusuma; Suwartini, Suwartini; Kirom, Hawis Ahmadul; Nafisyah, Khoirul; Wijaya, Aya; Ayona, Khansa Amalia (Community Empowerment, 2025)
The Special Region of Yogyakarta (DIY) faces a priority waste problem, with daily production exceeding 1000 tons. Vocational high schools (SMK) with Culinary Arts Programs contribute significantly to organic waste from practical activities. This community service program aimed to reduce waste production at the source (school level) by implementing a creative, circular economy-based project: the cultivation of Black Soldier Fly (BSF) maggots and tilapia. The methods applied included socialization, training, technology application, mentoring, and evaluation for teachers. The activity focused on training teachers to process school organic waste into BSF maggot feed, which was then utilized as feed for tilapia. The program evaluation results showed that 100% of the participating teachers understood and were able to practice the entire cultivation cycle of BSF maggots and tilapia. The teachers are also ready to disseminate this knowledge to students as a creative project. This program successfully created an effective, integrated food waste management model within the school environment.